Design and experimental Verification of Vibration Testing Fixture for Flight Control Panel - Wijaya, Yusuf Giri; Ula, Nur Mufidatul; P.P., Mikhael Gilang Pribadi; Muksin, Muksin; Syah, Agus Harno Nurdin (BRIN Publishing, 2021)
In this research, experimental design and testing of the vibration test fixture were carried out. The designed vibration test fixture is used to test the FCP, which is one of the components of avionics in aircraft. FCP vibration testing is carried out using the DO-160 test standard. The test has a test frequency range from 5 to 500 Hz. Therefore, the vibration test fixture must have a natural frequency above 600 Hz. The vibration test fixture is designed using a T-type model with modifications to get optimal results. The raw material used to make the test fixture is aluminum. The test fixture has a natural frequency value above 500 Hz, and both were tested using FEM simulation and experimental tests. Therefore, the vibration test fixture that is made meets the requirements for vibration testing on FCP. The difference in the natural frequency value from the FEM simulation and experimental test results on the vibration test fixture is 14.61% on the Z-axis, 10.61% on the X-axis, and 9.74 on the Y-axis.